Working with Asian Indian American Families: A Delphi Study - Khanna, Anchal; Mcdowell, Teresa; Perumbilly, Sebastian; Titus, Gayatri (Journal of Systemic Therapies, 2009)
In this paper, we contribute to an agenda of developing culturally informed practices, centering specifically on working with Asian Indian and Asian Indian American families. We report the results of a modified Delphi study in which we asked advanced members of the counseling field who are of Asian Indian origin to share their insight relative to family therapy with those who identify as Asian Indian or Asian Indian American in the U.S. Panelists offered a multitude of recommendations, including the importance of: careful assessment that acknowledges within group similarities and differences; attention to extended family ties and intergenerational dynamics; understanding issues of immigration, acculturation, and discrimination; and development of treatment approaches that are congruent with Asian Indian cultural values, beliefs, and practices.
Keywords: dept.mft; peer-reviewed

The Measurement of Outcome Variables in Couple and Family Therapy Research - Sanderson, Jessica; Kosutic, Iva; Garcia, Marisol; Melendez, Tatiana; Donoghue, Jamie; Perumbilly, Sebastian; Franzen, Caroline; Anderson, Stephen (The American Journal of Family Therapy, 2009)
Measurement constitutes a central issue in determining effectiveness of couple and family therapy (CFT). A review of 274 CFT outcome studies published in 25 mental health journals between 1990 and 2005 is presented. Goals of this review were to (1) provide a broad, empirically based overview of CFT outcome research, (2) examine measurement of treatment outcomes, and (3) appraise reporting practices. Findings indicate that a wide range of instruments continue to be used in CFT outcome research, although a foundation for a more integrated and coherent assessment battery has been established. Implications for the field are discussed.
Keywords: dept.mft; peer-reviewed

A new perspective: the common factors model as a foundation for social work practice education - Cameron, Mark; Keenan, Elizabeth King (Journal of Teaching in Social Work, 2009)
Foundation social work practice education is critical to the preparation of BSW practitioners for professional practice and the establishment of a theoretical and skill base upon which graduate students may build competencies in the advanced curriculum. Issues in the foundation practice curriculum may hinder this development. The common factors model holds promise as an organizing framework for foundation social work practice education. This model may help to resolve some key issues in social work and social work education, and may provide a useful, coherent, and empirical base for the foundation practice curriculum. © Taylor & Francis Group, LLC.
Keywords: Common factors; Direct practice; Foundation curriculum; Practice education; dept.swk; peer-reviewed

Teaching organization theory and practice: an experiential and reflective approach - Cameron, Mark; Turkiewicz, Rita M; Holdaway, Britt A; Bill, Jacqueline S; Goodman, Jessica; Bonner, Aisha; Daly, Stacey; Cohen, Michael D; Lorenz, Cassandra; Wilson, Paul R; Rusk, James (Journal of Teaching in Social Work, 2009)
The organization is often the overlooked level in social work's ecological perspective. However, organizational realities exert a profound influence on human development and well-being as well as the nature and quality of social work practice. This article describes a model of teaching organization theory and practice which requires master's social work students to assess their school of social work as well as their field placement agencies. Teaching organization theory and practice experientially may help students understand how organizations influence practice and empower them to see organization practice as a legitimate and important aspect of their work.
Keywords: Field education; Macro; Organization; Practice; Teaching; dept.swk; peer-reviewed